The Role of Lost Industrial Heritage in Urban Memory: The Case of Şükraniye Small Industrial Site - Aylin Güney; Gökçen Kılınç Ürkmez (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2025)
This study aims to open a discussion on the place and impact of lost industrial spaces in the construction of urban memory through the example of the Şükraniye Small Industrial Bazaar located in Yıldırım District, Bursa Province. Established in the 1960s, the Şükraniye Small Industrial Bazaar was an area hosting various workshops and eateries, including blacksmiths, weavers, cutlers, foundries, and turners, where many economic activities of the city took place. While the demolition of the Şükraniye Small Industrial Bazaar is regarded as a loss of memory, urban memory, through various witnesses, enables a new process of remembrance regarding the Industrial Bazaar. As a method, the study utilised planning decisions and cadastral data demonstrating the changes in the area from past to present. Additionally, interviews were conducted with individuals who witnessed the previous state of the area, and documents revealing the transformation process were evaluated. By emphasising the significance of the bazaar, which can be considered industrial heritage, within the city’s memory, the study will propose strategies to enable the bazaar to be revived within the urban memory and identity.